Metal Wall Thickness Assessment of Air Receivers by Method of Ultrasonic Testing (UTM) - Okpighe, SundayOkerekene; Ovri, James Ogagarojo; Ononuju, C. N. (International Journal For Research In Mechanical & Civil Engineering, 2016)
Metal Wall Thickness Assessment of Air Receivers by Method of Ultrasonic Testing (UTM) is reported. The Air Receivers were duly prepared for the assessment in line with the guidelines for UTM tests. The tests were carried out and results so obtained were documented in tabular and graphical arrays. The evidence of previous UTM assessments were unavailable, hence current data were referenced to the theoretically calculated base data. The results so generated, helped in forecasting the safety/integrity (fitness-for-service) by computing: The amount of metal loss anticipated before the next scheduled inspection (FCA);The remaining thickness ratio ( Rt ) and the length over which the thickness data may be averaged.